The Interpretation on Metaphors Presented in "Good 4 U" Song Lyrics by Olivia Rodrigo - Winora, Anisa; Arifin, M. Bahri; Sartika Dewi Max, Jonthan Irene (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
This research focuses on the interpretation of the use of metaphor in the Good 4 U song lyrics written by Olivia Rodrigo. The purpose of the study is to know what the interpretations of metaphors presented in Good 4 U song lyrics by Olivia Rodrigo are. This research is qualitative research and the results show that 6 categories of metaphors can be captured in Good 4 U song lyrics. Out of the 27 data, there are 2 absolute or paralogical metaphors, 1 dead metaphor, 4 extended metaphors, 5 indirect metaphors, 4 contextual metaphors, 10 root metaphors, and 1 metaphor that does not belong to the metaphor category. The researcher can conclude that the root metaphor is the most common metaphor found in the lyrics of the song Good 4 U. The interpretation of the lyrics of the song deals with (1) The destruction of the relationship, (2) The warmth of a past relationship, and (3) the sadness of the singer because she was ignored by her ex-boyfriend who achieved extraordinary success. From this research, it can be concluded that metaphors greatly affect the meaning of lyrics because they can convey a certain meaning better, which can help the listener understand what the composer is trying to say.Keywords: Metaphors, Song lyrics, Good 4 U, Olivia Rodrigo